ANALISIS KUAT SUMBER NEUTRON DAN PERHITUNGAN LAJU DOSIS NEUTRON TERAS AWAL RDE - Suwoto; Adrial, Hery; Zuhair (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The reactor core RDE (Experimental Power Reactor) has non-annular cylindrical shape with coated fuel particles TRISO kernel in the spherical form (pebble) and cooled by helium gas. The RDE reactor core design is very safe, because it adopts the high-temperature reactor technology (HTGR) with inherent passive safety. The designed input helium temperature of RDE core is about 250 °C and the output of helium gas temperature helium of the reactor core of 700 °C. Beside of generating electricity, the RDE reactor is designed to generate high temperature gas that can be used for any purposes such as cogeneration (heat process application research). The spherical fuel called as pebble containing thousand of kernel TRISO-coated fuel particles of uranium dioxide 17 % (235U) enriched. TRISO coating comprises four layers, namely: porous carbon buffer layer, inner part pyrolytic carbon layer (IPyC, Inner Pyrolitic Carbon), silicon carbide layer (SiC) and a layer of pyrolytic carbon outer part (OPyC, Outer Pyrolitic Carbon). Analysis of neutron source strength and preliminary calculation of neutron dose rate on the RDE core were performed using Monte Carlo MCNP5v1.2 code. Double heterogeneity treatment in TRISO-coated fuel particles kernel and the pebble of the core are applied. Utilization of EGS99304 code to determine 640 amount of energy group structures (SAND-II neutron group structures) are used in the neutron spectrum calculation in the reactor. The reactor core is divided into 100 zones (10 in radial and 10 in axial directions). An analyses calculation result shows that the neutron source strength of the core is about 8.47027X1017neutron/sec. The neutron dose rate distributions are determined using a conversion factor of flux-to-dose taken from International Commission on Radiological Protection (ICRP) and National Council on Radiation Protection and Measurements (NCRP). The preliminary calculations result of neutrons dose rate using ICRP-21 and NCRP-38 conversion factor for radiation workers in the radial direction in the shield biological are already weakened as low as 6.69915 and 6.9964 μSv/h, respectively, at a position of 215 cm from the center part of the core. This result analysis indicate that radiation workers are safe and protected from neutron radiation sources in accordance with the regulatory requirements. Overall, from the calculation and analysis, it appears that the radiation and biological shielding model meets to the standards of radiation safety required. The results of this study can be used to complete the design data thickness of shielding of the reactor.